HUBUNGAN MUTU LAYANAN LEMBAGA PENDIDIKAN TERHADAP TINGKAT KEPUASAN ORANGTUA SISWA - Kusumaningrum, Desi Eri; Triwiyanto, Teguh; Sumarsono, Raden Bambang; Arafik, Muh; Kulidtod, Zainal Dimaukom; Budiarti, Erika Mei; Putri, Septiani Cahyaning; Akhoba, Zoulhijjah Harinda (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2024)
The aim of this research is to analyze the relationship between quality/service variables and the satisfaction of parents of students in elementary schools throughout Diwek District. This research uses quantitative research methods with simple correlation analysis. The research sample was calculated based on the Slovin formula from the existing population, so that 100 parents of students were selected as the sample. The sample calculation was based on cluster sampling, namely the territorial division of the selected research locations from the north, west, south and east of Diwek District, Jombang Regency. Based on the calculation results obtained by the researcher, namely for hypothesis testing, the significance obtained for the two variables (Service Quality and Parental Satisfaction) was 0.000 where 0.000 < 0.05, "H1 was accepted and H0 was rejected" with the hypothesis conclusion being accepted. The meaning of the accepted hypothesis is that there is a significant relationship between institutional service quality (X) and student parent satisfaction (Y). So the conclusion of the research results is that there is a significant relationship between service quality and satisfaction of parents of students in public elementary schools in Diwek District, Jombang Regency.